Queering anarchism addressing and undressing power and desire - Daring, C. B. (AK Press, 2012)
"What does it mean to 'queer' the world? Queering Anarchism suggests that 'queerness' is more than a new gender norm--instead offering a new personal politics that refuses to acquiesce to the mainstream codification of LGBT identity. Using revolutionary anarchism's long tradition of social, political, and economic theory as a foil, these engaging essays bring together a diverse set of ideas ranging from the deeply theoretical to the playfully personal, and explore the myriad possibilities that the concept of 'queering' presents"--Back cover